Synthesis of Ecofriendly Detergent by Using White Dextrin Sorbitol Maleic Anhydride - Gogte, B.B.; Dontulwar, J.R. (Asian Journal of Chemistry, 2016)
Esters of carbohydrates have been synthesized by using white dextrin, sorbitol, maleic anhydride. This resin has shown favourable data for detergent synthesis. The detergent prepared has shown appreciable reduction of surface tension of water at different concentrations. This is the exclusive characteristic of the surfactant to reduce the surface tension of water. At concentrations 0.33 g, 0.25 g and 0.2 g per 100 mL of water, the detergent has shown 56.16, 35.31 and 27.77% reduction in surface tension of water respectively.